Philosophy of Tashrī‘ Review on Internalization Maja Labo Dahu in The Legal System of The Sultanate of Bima - Idrus, Achmad Musyahid; Hasan, Hamzah; Asti, Mulham Jaki; Taudiyah, Nasya Tisfa; Halim, Patimah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Maja Labo Dahu's philosophy represents the Bima community's local values that have been internalized into Islamic law. This research aims to find answers to the issues examined, namely the existence of Islamic law in the Sultanate of Bima. The primary focus lies in the analysis of the implementation of Islamic law during the Sultanate of Bima and the internalization of the philosophy of Maja Labo Dahu within the Sultanate of Bima. The method used in this research is a descriptive qualitative method, which explores written documents and information from Bima community figures who know the implementation of Islamic law in the Sultanate of Bima as a result of the internalization between the philosophy of Maja Labo Dahu and the fiqh tashrī' in Islam. The data used in this research were obtained through observation, cross-checking interviews, and literature study. The findings of this research reveal that Islamic law has existed in the Sultanate of Bima since Islam was accepted as the official religion, based on the legitimacy of the theory of shahada, which explains the application of Islamic law coinciding with the Bima community's embrace of Islam. However, formally and juridically, Islamic law was declared applicable throughout the Sultanate of Bima after the establishment of three legal institutions, namely Sara Tua, Sara Sara, and Sara hukum, which were responsible for coordinating the implementation of laws such as flogging, stoning, retribution, and discretionary punishment. The philosophy of Maja Labo Dahu has been internalized into the Islamic law of the Kingdom of Bima, causing the Bima community to feel fear and shame in committing legal violations. Keywords: Tashrī’ philosophy, Maja Labo Dahu, Family Law, Sultanate of Bima.